The Nature and Effects of Technological Change Over the Industry Life Cycle - Darren Filson (Claremont McKenna College, Department of Economics, 2000)
This paper estimates the nature and effects of quality and cost innovations in the early automobile, personal computer, rigid disk drive, computer monitor, and computer printer industries using industry-level data on firm numbers, price, quantity, and quality along with an equilibrium model of industry evolution. The results challenge the notion that new industries experience a pattern of quality innovation early on followed by cost innovation later on. In the four microelectronics industries the rate of quality improvement does not diminish as the industries evolve. The results for the automobilie industry demonstrate that even the when the rate of quality improvement is highest early on, the profitability of quality advantages may be higher later on.
Keywords: L10; L63; O31; 330; shakeout; product and process innovation; technological change; industry dynamics; technology